Techniques and Instrumentation for Detection of Exoplanets VIII 2017
DOI: 10.1117/12.2272775
|View full text |Cite
|
Sign up to set email alerts
|

Phase-shifting coronagraph

Abstract: With the recent commissioning of ground instruments such as SPHERE or GPI and future space observatories like WFIRST-AFTA, coronagraphy should probably become the most efficient tool for identifying and characterizing extrasolar planets in the forthcoming years. Coronagraphic instruments such as Phase mask coronagraphs (PMC) are usually based on a phase mask or plate located at the telescope focal plane, spreading the starlight outside the diameter of a Lyot stop that blocks it. In this communication is invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…To find an incident wavefront characteristic, we solve the inverse problem substantially easier. We found, however, much closer similarity of PSI with [25,26]. The interfero-coronagraph in Figure 2a has the 180 • scheme, the Figure 2b scheme has a variable rotational shift, and the Figure 2c scheme has a fixed angle of rotation shear.…”
Section: Wavefront Measurement By Means Interfero-coronagraph and Pha...supporting
confidence: 54%
See 1 more Smart Citation
“…To find an incident wavefront characteristic, we solve the inverse problem substantially easier. We found, however, much closer similarity of PSI with [25,26]. The interfero-coronagraph in Figure 2a has the 180 • scheme, the Figure 2b scheme has a variable rotational shift, and the Figure 2c scheme has a fixed angle of rotation shear.…”
Section: Wavefront Measurement By Means Interfero-coronagraph and Pha...supporting
confidence: 54%
“…To find an incident wavefront characteristic, we solve the inverse problem substantially easier. We found, however, much closer similarity of PSI with [25,26].…”
Section: Wavefront Measurement By Means Interfero-coronagraph and Pha...mentioning
confidence: 43%
“…So far, the most well-known PMCs probably are the Roddier and Roddier, four-quadrants, and vortex coronagraphs, whose diffractive properties were discussed extensively in Refs. [4] and [14]. They show that most of the starlight is redirected outside of the pupil area (as schematized by the orange beam in Figure 4-b), which entails the presence of a Lyot stop preventing starlight from reaching the science detector 1 .…”
Section: Phase Mask Coronagraphs (Figure 4-b)mentioning
confidence: 98%
“…Numerical simulations in Ref. [4] demonstrated that for efficient WFE reconstruction their apertures should be oversized by a factor of three at least. Such requirement may turn even more critical if a spectrograph has to be coupled with the coronagraph.…”
Section: Phase Mask Coronagraphs (Figure 4-b)mentioning
confidence: 99%
See 1 more Smart Citation